The role of pericarp in Bidens L. heterocarpy (Asteraceae) - Moura Souza-Filho, Paulo Roberto de; Bianchessi, Sarah Bayod [UNESP]; Yamaguchi, Lydia F.; Kato, Massuo J.; Coan, Alessandra Ike [UNESP]; Takaki, Massanori [UNESP] (Elsevier B.V., 2019)
Diaspore heteromorphism is a common reproductive strategy in Asteraceae. The genus Bidens L. contains some species with two or more types of cypselae in a single capitulum, with dicarpy being more frequently observed. Our work aims to address how the pericarp influences germination in heterocarpic species of Bidens. The species were assigned based on their morphophysiological features: dicarpic species included Bidens alba (L.) DC., B. aristosa (Michx.) Britton, B. bipinnata L., B. frondosa L., B. pilosa L., B. subalternans DC., and a polycarpic species included B. gardneri (Baker). We investigated the variation in cypselae via morphological measurements, pericarp anatomical analysis and secondary metabolites profile by high-performance liquid chromatography-mass spectrometry (HPLC-ESI+). The pericarp weight and the anatomical structures differed among the types of cypselae, but these differences cannot be assumed to represent a germination barrier. Nonetheless, principal component analysis indicated that the pericarp chemical composition varied among B. aristosa, B. bipinnata, B. pilosa, and B. subalternans. The analysis of metabolic profile of the pericarps revealed esculin, glycosylated flavonoids and nitrogenous compounds in all cypselae. Our work brings new evidence for understanding the way the pericarp influences the germination of heterocarpic species under anatomical and metabolomic frameworks. We discard the differential mechanical constraint as the main inducer of dicarpy for these Bidens species.
Keywords: Chemical inhibition; Heteromorphism; Mixed strategy; Physical constraints